Perancangan Sistem Aplikasi Tabungan Sekolah Pada SMK Tiara Bangsa dengan Menggunakan PHP dan MySQL - Zabna Delima (ALMUISY: Journal of Al Muslim Information System, 2024)
Tiara Bangsa Vocational High School is a foundation that operates in the field of education and is an institution that requires the development of information and communication technology. One of the problems with the school savings system at Tiara Bangsa Vocational School is that it still uses books to record student names, deposit data and withdrawal data as well as student transaction reports. Using books to record savings takes a long time, the books used can be lost or torn and require a special place to store these books. This school savings information system was developed using the PHP and MySQL programming languages. This Web-based student savings information system research aims to produce a school savings information system application that is able to overcome the problem of managing school savings at Tiara Bangsa Vocational School so that the system that is currently being implemented can switch to a computerized system using a school savings information system application. Keywords: Design, school savings information system, PHP, MySQL